Optimization of the parameters for surface quality of the open-source 3D printing - Sukindar, Nor Aiman; Mohd Ariffin, Mohd Khairol Anuar; Baharudin, B.T Hang Tuah; Jaafar, Che Nor Aiza; Ismail, Mohd Idris Shah (Faculty of Mechanical Engineering,Universiti Teknologi MARA (UiTM), Malaysia, 2017)
Fused deposition modeling (FDM) or three-dimensional (3D) printing are becoming ubiquitous today because it allows the fabrication of 3D products directly from computer-aided design software. The quality of 3D parts is influenced by several parameters that need to be carefully tuned to obtain a high-quality final product. The surface finish of the finished parts is one of the major factors to consider because it affects both the dimensional accuracy and the functionality of the piece. Thus, the present study focuses on improving the surface finish of parts produced by FDM by manipulating different parameters such as layer height, raster angle, extruder temperature, printing speed, and percent infill. Polylactic acid was used for this study, which is a material present in filament form, and was extruded using a newly developed 3D printer; the Taguchi’s 35 design-of-experiment method was used to design the experiment. The results indicate that raster angle, extruder temperature, and layer thickness are the most influential process parameters of the surface quality of the final product.